Adolescents’ experience of receiving internet-delivered cognitive therapy for social anxiety disorder - Leigh, E; Nicol-Harper, R; Travlou, M; Clark, D (Elsevier, 2023)
Background: Social anxiety disorder (SAD) is a debilitating condition that usually begins in adolescence. We recently demonstrated preliminary efficacy of an internet-delivered therapist-assisted version of Cognitive Therapy for Social Anxiety Disorder (SAD) for adolescents called Online Social anxiety Cognitive therapy for Adolescents (OSCA). Here we report on the helpfulness, support, and overall acceptability of OSCA from the perspective of trial participants.